Мистецтво зупиняє час. Про актуальні передумови ідей Артура Шопенгауера - Гриґель, Т. (Студії мистецтвознавчі, 2008)
The essential feature of the present is a constant race against time, cult and fetishization of time, which destroys the privacy of life of an individual, the natural course of this individual’s activity, and even devastates the sphere of culture.